THE EFFECT OF RETURN ON EQUITY, EARNING PER SHARE, AND DEBT TO TOTAL ASSET RATIO ON STOCK PRICE IN INDUSTRY LISTED ON IDX - Arsyad Paweroi (Sekolah Tinggi Pariwisata Mataram, 2021)
The research objective is to determine the effect of ROE, EPS, and DAR on stock prices. This study took a sample of the ceramic, porcelain, and glass sub-sector industrial companies listed on the IDX with an observation period from 2015-2019. The analytical method uses quantitative descriptive with secondary data obtained from the Indonesia Stock Exchange. Data collection using the documentation method. The data analysis technique used is multiple regression. The results of this study indicate that there was a simultaneous significant influence between EPS, ROE, and DAR variables on stock prices in the ceramic, porcelain, and glass sub-sector industry. The EPS variable had a partially significant effect on stock prices, while the ROE and DAR variables did not have a partially significant effect on stock prices.